PENGARUH BIAYA AUDIT, TEKNOLOGI INFORMASI DAN KOMPETENSI AUDITOR TERHADAP KUALITAS AUDIT SELAMA COVID-19 - Indra Indra; Rindu Rika Gamayuni; Usep Syaipudin (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2021)
The Corona Virus Disease (COVID-19) is endemic in Indonesia and affects many sectors, including the economic and government sectors. During the COVID-19 pandemic, BPK, as the government’s external auditors, continued to carry out the audit to maintain accountability for state finances despite budget refocusing and large-scale social restrictions (Pembatasan Sosial Berskala Besar, PSBB). This study aims to determine the significance of audit costs due to budget refocusing, IT utilization, and auditor competence on audit quality during the work from home (WFH) policy. This study processed questionnaire data from 70 auditors from three representative offices of BPK in provinces under three different categories, namely A, B, and C. The research data was processed using SmartPLS software to analyze data with measurement models and structural models with a 90 percent confidence level. Data processing shows that the effect of audit costs and the use of information technology on audit quality during the COVID-19 pandemic has a feeble and insignificant effect; thus, the hypothesis is not supported. Meanwhile, the competence of auditors has a significant effect on the quality of audit results; ergo, the hypothesis is supported.